The role of synchronous tools in online learning practices after the pandemics - Seixas, Sónia (2021)
The Covid-19 pandemics had most impact on face-to-face education, but online learning was not immune to the changes in all our lives caused by the situation. Imposed lockdown led to greater use of and familiarization with web conferencing technologies, potentially intensifying and driving new ways to learn and communicate in the context of distance education. In this paper we report on a survey on master's students perceptions of the use of synchronous tools in a distance teaching university, before and during the pandemics. The results indicate that students are more comfortable with tools like Zoom, and that they help them to better relate with teachers and classmates, improving their learning.